Dreaming of a Brighter Future? The Impact of Economic Vulnerability on University Aspirations - Barry Watson; Nancy Kong; Shelley Phipps (Institute of Labor Economics (IZA), 2022)
We examine whether there is an inequality of opportunity to achieve higher education, partially explained by aspirations for youth age 12-15 in economically vulnerable households. Using a unique Canadian dataset (2002-2008), we find that poverty is associated with reduced university aspirations from the perspective of the youth and their mother. Further, poverty depth matters less than incidence. In terms of magnitude, poverty contributes to about 10-15 percent of the observed inequality of opportunity gap (mother's education being the largest factor at 30 percent). Interestingly, economic insecurity is not associated with educational aspirations, and this result persists regardless of how we measure insecurity. Controls for academic effort, including standardized test scores, daily reading, and getting good grades do not impact these findings. Results therefore suggest that alleviating child poverty and easing post-secondary financial barriers among the poor, may help offset reduced university aspirations at a critical time in a youth's life.
Keywords: I21; I23; I24; I32; D63; 330; education; aspirations; poverty; economic insecurity; inequality of opportunity